Casos y cosas: semanario popular (Vol. 2, No. 57) - Imprenta La Region (My University, 1920)
SPANISH: Incluye: Un poco de todo, Como los saltadores, Correo franco y con franqueza, El beso, Buzón, Una reja que se esfuma, Por esos mundos.

ENGLISH: Includes: A little bit of everything, Like the jumpers, Franco mail and with frankness, the kiss, Mailbox, A grille that vanishes, For those worlds.
Cases and things: popular weekly magazine (Vol. 2, No. 57)
Keywords: Periodicals; Satire, Peruvian; Humor; Iquitos (Perú)--revistas; Perú--revistas satíricas